Methane production from organic acids obtained by supercritical water treatment of Japanese beech [Fagus crenata] - Yoshida, K., Kyoto Univ. (Japan); Miyafuji, H; Saka, S (Journal of Wood Science, 2010)
Japanese beech (Fagus crenata) wood was treated in supercritical water at 380degC/30 MPa and 380degC/100 MPa. The hydrolysate (water-soluble portion) was found to contain the fragmented and dehydrated compounds of sugars and organic acids. Although organic acids are expected to be utilized for methane fermentation, the effects of the fragmented and dehydrated compounds of sugars on methane production are not known. The objective of this study is, therefore, to elucidate the potential of supercritical water treatment as a new pretreatment for methane production by evaluating the methane fermentability of the hydrolysate. From the methane fermentation tests for those model compounds with digested sludge, it is found that methane was produced not from the fragmented and dehydrated compounds but from the organic acids. The yield of methane from the hydrolysate obtained at 380degC/30 MPa was higher than that from the hydrolysate obtained at 380degC/100 MPa because the former contains more organic acids than the latter. The maximum yield of methane was seven times greater compared to the untreated wood, indicating that the supercritical water treatment is effective for enhancing the productivity of methane from wood.